Risks, benefits, and knowledge gaps of non-native tree species in Europe - Dimitrova, Anastazija; Csilléry, Katalin; Klisz, Marcin; Lévesque, Mathieu; Heinrichs, Steffi; Cailleret, Maxime; Andivia, Enrique; Madsen, Palle; Böhenius, Henrik; Cvjetkovic, Branislav; De Cuyper, Bart; de Dato, Giovanbattista; et al. (Frontiers in Ecology and Evolution, 2022)
Changing ecosystem conditions and diverse socio-economical events have contributed to an ingrained presence of non-native tree species (NNTs) in the natural and cultural European landscapes. Recent research endeavours have focused on different aspects of NNTs such as legislation, benefits, and risks for forestry, emphasizing that large knowledge gaps remain. As an attempt to fulfill part of these gaps, within the PEN-CAFoRR COST Action (CA19128) network, we established an open-access questionnaire that allows both academic experts and practitioners to provide information regarding NNTs from 20 European countries. Then, we integrated the data originating from the questionnaire, related to the country-based assessment of both peer-reviewed and grey literature with information from available datasets (EUFORGEN and EU-Forest), which gave the main structure to the study and led to a mixed approach review. Finally, our study provided important insights into the current state of knowledge regarding NNTs. In particular, we highlighted NNTs that have shown to be less commonly addressed in research, raising caution about those characterized by an invasive behaviour and used for specific purposes (e.g., wood production, soil recultivation, afforestation, and reforestation). NNTs were especially explored in the context of resilient and adaptive forest management. Moreover, we emphasized the assisted and natural northward migration of NNTs as another underscored pressing issue, which needs to be addressed by joint efforts, especially in the context of the hybridization potential. This study represents an additional effort towards the knowledge enhancement of the NNTs situation in Europe, aiming for a continuously-active common source deriving from interprofessional collaboration.